Mocca-survey Database I: Galactic globular clusters harbouring a black hole subsystem - Askar, Abbas; Arca Sedda, Manuel; Giersz, Mirek (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. There have been increasing theoretical speculations and observational indications that certain globular clusters (GCs) could contain a sizeable popul